Construction and rationing of the handball repelling wall test for young players (Journal of the College of Basic Education, 2022)
The study aimed to build tests for some of defensive skills of handball young players .the researcher hos used descriptive method with scaning style as it suits the nature of research and its goals and represents the research society . The research community by young players registered for handball Iraqi union for the season 2015-2016 with the ages 17-18 years . the total number was 98. As the researcher built and rationing news is defensive (test bulwark), After the implementation of the tests in accordance with the scientific steps in the construction, As well as the building standards and levels of standard tests, the researcher suggested: -The researcher build and codify new tests are defensive (defensive moves test, test bulwark).enables the researcher to put grades and levels of standard tests.emerged from the search results that the largest proportion of respondents were in the middle, above the standard level of performance skill to the test defensive moves either test bulwark, was the biggest percentage below the waist.As the researcher recommends:In light of the findings of the researcher recommends the following:1.taking care of defensive tests which simplify choosing and determining process of the game players centers according to what these centers demand .The use of tests which found them a researcher.3.making researches and similar other studies on different speciments (various ages ) especially the tests and evaluation of defensive side totally for handball players.